An Analysis of mood used by Ali and Amirah in She wore red trainers novel : A systemic functional Grammar Approach - Naba Maulida Lumaksita (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2022)
et,1/adil,c.1